The Influence of Corticosteroids, Immunosuppressants and Biologics on Patients With Inflammatory Bowel Diseases, Psoriasis and Rheumatic Diseases in the Era of COVID-19: A Review of Current Evidence - Zhang, Mengyuan; Bai, Xiaoyin; Cao, Wei; Ji, Junyi; Wang, Luo; Yang, Yang; Yang, Hong (Frontiers in Immunology, 2021)
Patients with immune-mediated inflammatory diseases treated with corticosteroids, immunomodulators and biologics might face additional risk during COVID-19 epidemic due to their immunocompromised status. However, there was still no unanimous opinion on the use of these therapy during COVID-19 epidemic. Current studies suggested that systemic corticosteroids might increase the risk of hospitalization, as well as risks of ventilation, ICU, and death among patients with immune-mediated inflammatory diseases. And anti-TNF agent was associated with lower rate of hospitalization, as well as lower risks of ventilation, ICU, and death. No significant changes in rates of hospitalization, ventilation, ICU and mortality were observed in patients treated with immunomodulators or biologics apart from anti-TNF agents. The underlying mechanism of these results might be related to pathway of antiviral immune response and cytokine storm induced by SARS-COV-2 infection. Decision on the use of corticosteroids, immunomodulators and biologics should be made after weighing the benefits and potential risks based on individual patients